Al-Zamakhsharī’s Rational Hermeneutics and Social Ethics: An Analytical Study of Tafsīr Al-Kashshāf - Hazmin, Moh. Minhaji; Mochammad Yahya Ghozali (Journal of Ushuluddin and Islamic Thought, 2023)
The Mu‘tazilah school of thought has played an important role in Islamic theology, especially in discussions about social and ethical issues. One of the well-known interpretations that reflects this thought is Tafsīr al-Kashshāf by al-Zamakhsharī, which takes a rational and critical approach to understanding the verses of the Qur’an. In today’s world, many social issues, such as justice, individual freedom, and human rights, are closely related to Mu‘tazilah principles. This study focuses on how al-Zamakhsharī interprets Qur’anic verses related to social and ethical issues from a Mu‘tazilah perspective. The main source of the study is Tafsīr al-Kashshāf, while additional references include books and articles discussing tafsīr and Mu‘tazilah theology. A descriptive-analytical approach is applied to understand how al-Zamakhsharī structures his arguments and how Mu‘tazilah principles are reflected in his interpretation. The results show that Tafsīr Al-Kashshāf strongly represents Mu‘tazilah beliefs, especially in its emphasis on justice and human freedom. Al-Zamakhsharī highlights the importance of reason in understanding the Qur’an and rejects the idea that fate completely determines human actions. Additionally, among the five core principles of Mu‘tazilah, three are particularly important in shaping moral and ethical values: al-‘adl (divine justice), al-wa‘d wa al-wa‘īd (divine reward and punishment), and amar ma’rūf nahi munkar (encouraging good and preventing evil).